The Compliance in Paying Zakat Obligation: an Assessment of its Predictors - Yuliana Saputri; Ratna Mulyany (Proceedings of AICS - Social Sciences, 2021)
This study is aimed to determine what motivates zakat payers (Muzakki) in fulfilling their obligation to pay zakat at an authorized zakat institution such as Baitul Mal. Specifically it seeks to examine the effect of service, transparency and accountability on muzakki’s compliance in paying zakat. The data used in this study were obtained by distributing 98 questionnaires to muzakki in Lhokseumawe, which is one of the most populated regencies in Aceh Province, Indonesia. The final sample constitutes 84 respondents. Data was analyzed using multiple linear regression using the IBM SPSS Statistics 24 application. The result showed that service, transparency and accountability have a simultaneous effect on the payers (muzakki) compliance in paying zakat mal in Baltul Mal Lhokseumawe, while service has a positive effect on muzakki compliance in paying zakat mal. Interestingly transparency has no effect on muzakki’s compliance in paying zakat mal, and likewise accountability has no influence on muzakki’s compliance in paying zakat mal.Keywords: Service, Transparency, Accountability, Compliance, and Zakat Mal.